A critical Examination of Ball Thrift Trade in Islamic Law: A Sadd ad-Dzari'ah-Based Assessment of Used Garment Imports - Nadiyah Rofika; Suliyanto Suliyanto; Zulfa Rasyidah (Al-Fiqh: Journal of Contemporary Islamic Law, 2026)
This study aims to critically examine the legal and socio-economic implications of ball thrift trade in Indonesia using the principle of Sadd ad-Dzari’ah in Islamic law. The rapid growth of second-hand clothing imports has raised concerns regarding transparency, public health, and the protection of domestic industries. Many transactions occur with minimal regulatory oversight, exposing consumers and society to potential harm while benefiting low-income households economically. This research employs a normative legal research design with a qualitative approach, analyzing Islamic jurisprudence, scholarly literature, fatwas, and relevant regulations to evaluate the permissibility and consequences of ball thrift trade. The findings indicate that Sadd ad-Dzari’ah provides a preventive framework to block transactions that may lead to harm, emphasizing the need for regulatory caution; the inherent gharar in opaque bales can mislead consumers and increase health risks, including microbial contamination and chemical exposure; and illegal imports result in significant state revenue losses and negatively affect domestic textile industries, contributing to unemployment and decreased GDP. This study contributes to Islamic commercial law and public policy by integrating normative fiqh principles with practical considerations, recommending stricter transparency requirements, hygiene standards, and enforcement.